The Household Finance and Consumption Survey: methodological report for the second wave (European Central Bank (ECB), 2016)
At the end of 2006, the ECB Governing Council set up the Household Finance and Consumption Network (HFCN). The network is composed of researchers, statisticians and survey specialists from the ECB, European national central banks (NCBs), some national statistical institutes (NSIs), and a number of experts in the field of household finances who act as consultants. The mandate given to the HFCN is to develop and conduct the Eurosystem Household Finance and Consumption Survey (HFCS), and act as a forum for research with the survey data. While participation in the HFCN is purely voluntary, all euro area NCBs contribute to the HFCN and conduct the survey in their respective countries. In addition, several non-euro area NCBs participate as observers and, starting in the second wave, conducted the survey.
Keywords: C83; D31; 330; assets; distribution; households; liabilities; survey; wealth